Association between the basal ganglia and large-scale brain networks in epilepsy - Rektor, Ivan; Tomčík, Jan; Mikl, Michal; Mareček, Radek; Brázdil, Milan; Rektorová, Irena (Brain topography, 2013)
Epilepsy may affect connectivity between the putamen and cortex even during the resting state. Putamen is part of the basal ganglia resting state network (BG-RSN) which is anti-correlated with the default mode network (DMN) in healthy subjects. Therefore, we aimed at studying the functional brain connectivity (FC) of the putamen with the cortical areas engaged in the DMN as well as with the primary somatomotor cortex which is a cortical region engaged in the BG-RSN. We compared the data obtained in patients with epilepsy with that in healthy controls (HC). Functional magnetic resonance imaging (fMRI) was performed in 10 HC and 24 patients with epilepsy: 14 patients with extratemporal epilepsy (PE) and 10 patients with temporal epilepsy (PT). Resting state fMRI data was obtained using the 1.5 T Siemens Symphony scanner. The Group ICA of fMRI Toolbox (GIFT) program was used for independent component analysis. The component representing the DMN was chosen according to a spatial correlation with a mask typical for DMN. The FC between the putamen and the primary somatomotor cortex was studied to assess the connectivity of the putamen within the BG-RSN. A second-level analysis was calculated to evaluate differences among the groups using SPM software. In patients with epilepsy as compared to HC, the magnitude of anti-correlation between the putamen and brain regions engaged in the DMN was significantly lower. In fact, the correlation changed the connectivity direction from negative in HC to positive in PE and PT. The disturbed FC of the BG in patients with epilepsy as compared with HC was further illustrated by a significant decrease in connectivity between the left/right putamen and the left/right somatomotor cortex, i.e. between regions that are engaged in the BG-RSN. The FC between the putamen and the cortex is disturbed in patients with epilepsy. This may reflect an altered function of the BG in epilepsy.
Keywords: Epilepsy; Magnetic Resonance Imaging; mozek; magnetická rezonanční tomografie; epilepsie; Humans; Case-Control Studies; motorické korové centrum; lidé středního věku; mapování mozku; Nerve Net; studie případů a kontrol; epilepsie temporálního laloku; Putamen; Female; dospělí; lidé; putamen; mozková kůra; Cerebral Cortex; Brain Mapping; Adult; bazální ganglia; ženské pohlaví; Male; Middle Aged; Brain; Motor Cortex; Epilepsy, Temporal Lobe; Basal Ganglia; nervová síť; mužské pohlaví